The Supportive Role of Companion Midwife on Maternal and Newborn Outcomes in Primiparous Women: A Retrospective Cost Analysis in Yazd - Mohammad Zarezadeh; Fatemeh Zareian; Mehdi Raadabadi; Seyed Masood Mousavi; Moslem Taheri Soodejani; Maryam Dafei (Shahid Sadoughi University of Medical Sciences, 2023)
Background: The World Health Organization recommends that women be continuously supported by a favorite companion during labor. Currently, there is no strong evidence on specific support measures by midwifery in relation to improving the delivery process. Methods: The present retrospective cost analysis study was conducted during 2021-2022. The reports of 243 deliveries were checked in the patients' files in selected hospitals of Yazd city. Data analysis was done using SPSS26. Results: According to the study objectives, the desired delivery outcomes included type of delivery, postpartum complications, postpartum bleeding, and length of the active phase of labor, resuscitation of the newborn, hospitalization of the newborn, and Apgar score of the newborn in the first and fifth minutes. There was a statistically significant difference in delivery, postpartum complications, length of the active phase of labor and hospitalization of the newborn in the neonatal unit, resuscitation of the newborn, and the amount of nutrition of the exposed group compared to the non-exposed group. Among the desired performance indicators, patient length of stay and total cost per person between the exposure and non-exposure groups, the mean score of the cost per person had a statistically significant difference between the two groups (P<0.001). Conclusion: Generally, the presence of a companion midwife next to the mother in the delivery room improves some of the outcomes of the mother and the baby. It is recommended to carry out studies in this field along with checking mothers' satisfaction with companion midwives.